(untitled) - Galbraith, V. H. (London, 1964)
This book is divided into three parts, intended to present the mastering of history as an expanding revelation. The first part gives a rapid survey of the available materials and the mesns of sifting and testing them. The second deals with the difficulties inherent in historical research, nad the need to preserve and print the original sources. In the third the author gives a practical example of the application to a specific problem of historical methods and techniques.
Keywords: History,Historiography; Study and teaching